PENENTUAN NILAI KOEFISIEN SERAPAN BAHAN PADA BESI, TEMBAGA DAN STAINLESS STEEL SEBAGAI BAHAN PERISAI RADIASI - Iwan Setiyawan; Heri Sutanto; K Sofjan Firdausi (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2015)
Radiation shield is used to protect both workers and the general public from radiation. In Indonesia there are a lot of potential materials to be used as radiation shielding materials, such as iron, stainless steel and copper which these metals have a certain density and atomic number above 26. For the determination of the value of research material absorption coefficient and radiation dose on ferrous materials, stainless steel and copper as a radiation shield. The study was conducted at RS Happy land Yogyakarta using x-ray radiation source. In testing the absorption coefficient of the material in lead , iron , copper and stainless steel : The plane was set at a voltage, current and time on the conditions of 80 kV 32 mAs and 90 kV 40 mAs were fixed and the distance between the focus to the object as far as 100 cm, Multi Purpose Detector ( MPD ) was placed under the object, wide open field irradiation 5 cm x 5 cm, the center beam was placed right in the middle of the next object do exposure for each thickness of lead, iron, copper and stainless steel was done in sequence according to the thickness variation material. From the test results coefficient absorption material (µ) in iron, copper and stainless steel on condition exposure factor 80 kV 32 mAs showed μ for iron absorption coefficient of 0,76 / mm, copper of 1,16 / mm and stainless steel for 0,83 / mm. Results equality between iron, copper and stainless steel with lead to 1,3 mm thickness. Iron 8,9 mm, 5,8 mm copper and stainless steel 8,1 mm. Lead to a thickness of 2 mm, 13,7 mm iron, copper, stainless steel 8,9 mm and 12,5 mm. On condition exposure factor 90 kV 40 mAs showed μ for iron of 0,56 / mm, copper 0,92 / mm and stainless steel of 0,62 / mm. Results equality between iron , copper and stainless steel with Lead to a thickness of 2 mm, 17,5 mm iron, copper and stainless steel 10.6 mm 15,7 mm. Keywords: X - ray Unit, Multi Purpose Detector ( MPD ), Absorption Coefficient, Iron, Copper, Stainless Steel